Repair of severe aortic coartaction in the first three months of life. - Nozar, José; Duhagon, Pedro; Pagliari, Luis; Roure, Jorge; Surraco, José L; Zwim, Gizella; Canessa, Roberto; Badano, José L (Cirugía del Uruguay, 1988)
Between March 1982 and June 1984, eleven infants who were less than three rnonths old underwent repair operations of severe aortic coartaction in the Unit of Pedíatric Surgery at the Hospital Italiano ín Montevideo.